Sector-wide Circularity Assessment - Construction Sector - Bellstedt, Carolin; Athanassiadis, Aristide; de Groot, Rob; Hellemans, Adriaan; Chaudhry, Shamita; Martín Carreño, Gerardo Ezequiel; Malk, Vuokko; Rodriguez, Santiago; Cruces, Pedro (Zenodo, 2023)
This current Sector-Wide Circularity Assessment report provides contextual information on the three different CityLoops cities and their construction sectors under study. It then illustrates how circular these sectors are through circularity indicators and a Sankey diagram. Finally, it analyses and interprets the results, presents the limitations of the data used and offers recommendations on how to make this sector more circular. The assessment was carried out by the cities themselves after receiving extensive training on data collection and data processing . Numerous additional insights can be found in the individual Data Hubs of each city.